Brincar e formação docente: um estudo a respeito de brinquedotecas universitárias brasileiras (1984 a 2022) - Jorge, Beatriz Fernanda (2023)
The historical process of education is also related to the concepts built on the ludic and playing over time and the impacts of the same events on the conception of childhood and humanity. Understanding that these processes are interconnected to different aspects of society (cultural, economic, political, etc.), history becomes very relevant to understanding the relationship between changes in the social environment and how humanity is built and related. In this work, the study focus on the toy library, an environment where one can observe and reflect on how social relationships take place, from demands that emerge from communities and in group coexistence through the ludic and play. Thinking about this space in the course of history and occupying the places of research, the way events are recorded are also crucial to understanding social relations and their directions. The research proposes a mapping of Brazilian university toy libraries (from 1984 to 2020) and their conceptions about playing, promoting a historical analysis of their construction process and reflecting on the space of the toy library and teacher training. It is established a dialogue with the university toy library as a space for playing, emerging a relationship with culture as a social factor and a formative aspect, in the construction of knowledge, in public policies and in the strengthening of social relations through playfulness, playing and toys. The research has a qualitative character, using bibliographic analysis in the state of knowledge, documents and public policies and interviews to achieve its objectives.